Competitiveness of Brazilian tropical wood on the international market - Souza, Sandro Nogueira de (2018)
This work analyses Brazilian tropical wood exports, taking into consideration their performance and competitiveness from 2004 to 2011. The present paper aims to: a) determine the competitiveness of exports of goods: sawn wood and tropical plywood; and b) compare the performance of both products. The Constant Market Share model and the Revealed Comparative Advantage Index (RVAI) estimated competitiveness and performance. The results show that sawn wood has proven to be the only product to provide competitive gains over the analyzed period.